2020
DOI: 10.1007/s41748-020-00161-x
|View full text |Cite
|
Sign up to set email alerts
|

Projected Change in Temperature and Precipitation Over Africa from CMIP6

Abstract: We analyze data of 27 global climate models from the sixth phase of the Coupled Model Intercomparison Project (CMIP6), and examine projected changes in temperature and precipitation over the African continent during the twenty-first century. The temperature and precipitation changes are computed for two future time slices, 2030–2059 (near term) and 2070–2099 (long term), relative to the present climate (1981–2010), for the entire African continent and its eight subregions. The CMIP6 multi-model ensemble projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
197
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(241 citation statements)
references
References 72 publications
43
197
1
Order By: Relevance
“…Over the western Sahel, monsoon precipitation tends to move southward. Although at a weaker intensity, similar changes have been obtained at a near-term time horizon (i.e., over the period 2010-2049) (Monerie et al, 2017) and with the RCP4.5 emission scenario (Monerie et al 2012;Akinsanola and Zhou 2018), and the CMIP6 Shared Socioeconomic Pathways (Almazroui et al 2020;Monerie et al 2020).…”
Section: Sahel Precipitation Forced Response To Global Warmingsupporting
confidence: 67%
See 1 more Smart Citation
“…Over the western Sahel, monsoon precipitation tends to move southward. Although at a weaker intensity, similar changes have been obtained at a near-term time horizon (i.e., over the period 2010-2049) (Monerie et al, 2017) and with the RCP4.5 emission scenario (Monerie et al 2012;Akinsanola and Zhou 2018), and the CMIP6 Shared Socioeconomic Pathways (Almazroui et al 2020;Monerie et al 2020).…”
Section: Sahel Precipitation Forced Response To Global Warmingsupporting
confidence: 67%
“…Fontaine et al (2011b) have shown that a robust pattern emerges over the Sahel in response to global warming, with the majority of CMIP3 climate projections showing an increase in central Sahel precipitation and a decrease in western Sahel precipitation. This has also been shown within the CMIP5 ensemble (Monerie et al 2012(Monerie et al , 2013(Monerie et al , 2016Biasutti 2013;Roehrig et al 2013;James et al 2015;Diallo et al 2016;Gaetani et al 2017;Akinsanola and Zhou 2018;Dunning et al 2018) and the CMIP6 ensemble (Almazroui et al 2020;Monerie et al 2020). The multi-model ensemble also projects a modulation of the seasonal cycle of Sahel precipitation, with a decrease over the western Sahel occurring mainly during the early Sahel rainy season (i.e., May-June-July-August) and an increase over the central Sahel occurring mainly during the last months of the Sahel rainy season (i.e., August-September-October) (Biasutti 2013;Seth et al 2013;Monerie et al 2016;Dunning et al 2018).…”
Section: Introductionsupporting
confidence: 65%
“…The looming water crisis across the world should be faced by using ancient knowledge and technologies inherited from history, in addition to modern day achievements [101][102][103][104], to deal with water scarcity, especially in developing countries. The use of qanats and cisterns can be implemented nowadays, especially where these systems are lacking, in order to strive for the sustainability of water resources [56].…”
Section: Resultsmentioning
confidence: 99%
“…The CMIP data are obtained from climate change reports of the Intergovernmental Panel on Climate Change and provide important references. They have been widely used in the fields of meteorology (Priestley et al, 2020;Zhu et al, 2020), hydrology (Almazroui et al, 2020), ocean research (Grise and Davis, 2020) and others. The CMIP6 datasets included 11 models obtained under four climate change scenarios in 2015-2065 ( Table 1).…”
Section: Datamentioning
confidence: 99%